Being a Rhythm Analyst in the City of Varanasi - Tiwari, Reena (Springer, 2008)
The way in which we perceive various spaces in the city and the way our bodies inhabit them affects the way we conceive the city. Hence, there are links between methods of seeing, inhabiting and representing the city and the manner in which they are designed. Yet, as Lefebvre has suggested, architects and planners have often ignored the way these spaces are read and inhabited or lived. By ignoring the lived aspect of space, the role of the user in constructing and representing or mapping the city space is completely overlooked. This article discusses rhythm analysis as a technique for constructing experiential maps by using a case study of Varanasi, which is an Indian city seeped in traditions and where one can find an intense relationship between user’s body, space and its representation.